Cancer cachexia: Are we ready to take a step forward?. Issue 3 (4th December 2017) - Crawford, Jeffrey
Abstract : The field of cancer cachexia at both the preclinical and clinical levels will benefit from the further investigation and refinement of its mechanisms and further study of potential agents to define the best treatment outcomes for patients. In the meantime, the availability of anamorelin, a promising agent in the clinic, would be extremely valuable to move that research forward. See also pages 606‐16.